Agrobacterium tumefaciens-mediated transformation of Cleome gynandra L., a C(4) dicotyledon that is closely related to Arabidopsis thaliana - Newell, Christine A. (Oxford University Press, 2010)
In leaves of most C(4) plants, the biochemistry of photosynthesis is partitioned between mesophyll and bundle sheath cells. In addition, their cell biology and development also differs from that in C(3) plants. We have a poor understanding of the mechanisms that generate the cell-specific accumulation of proteins used in the C(4) pathway, and there are few genes that have been shown to be important for the cell biology and development of C(4) leaves. To facilitate functional analysis of C(4) photosynthesis, and to enable knowledge from Arabidopsis thaliana to be translated to C(4) species, an Agrobacterium tumefaciens-mediated transformation protocol was developed for the C(4) species Cleome gynandra. A. tumefaciens, harbouring the binary vector SLJ1006, was used to transfer the uidA gene under the control of the CaMV 35S promoter into C. gynandra. Co-incubation of hypocotyls or cotyledons with SLJ1006 allowed efficient transfer of DNA into C. gynandra, and media that allowed callus production and then shoot regeneration were identified. Stable transformants of C. gynandra with detectable amounts of β-glucuronidase (GUS) were produced at an efficiency of 14%. When driven by the CaMV 35S promoter, GUS was visible in all leaf cells, whereas uidA translationally fused to a CgRbcS gene generated GUS accumulation specifically in bundle sheath cells. This transformation procedure is the first for an NAD-ME type C(4) plant and should significantly accelerate the analysis of mechanisms underlying C(4) photosynthesis.